Presence of Serum Antinuclear Antibodies Does Not Impact Long-Term Outcomes in Nonalcoholic Fatty Liver Disease. (August 2020) - Younes, Ramy; Govaere, Olivier; Petta, Salvatore; Miele, Luca; Tiniakos, Dina; Burt, Alastair; David, Ezio; Vecchio, Fabio M.; Maggioni, Marco; Cabibi, Daniela; Fracanzani, Anna L.; Rosso, Chiara; et al.
Abstract : INTRODUCTION: We investigated the longitudinal impact of antinuclear antibody (ANA) on clinical outcomes and survival in nonalcoholic fatty liver disease (NAFLD). METHODS: ANA were found in 16.9% of 923 biopsy-proven NAFLD patients, but none of them had histologic autoimmune hepatitis (AIH) or developed AIH after a mean follow-up of 106±50 months. RESULTS: Although ANA-positive cases had a higher prevalence of nonalcoholic steatohepatitis at baseline, the occurrence of liver-related events, hepatocellula carcinoma, cardiovascular events, extrahepatic malignancy, and overall survival were similar to ANA-negative. DISCUSSION: Once AIH has been ruled out, the long-term outcomes and survival are unaffected by the presence of ANA in patients with NAFLD.